Preparation method of modified carbon fiber composite material

By modifying carbon fiber and cellulose and chemically cross-linking it with polyurethane, the problem of poor compatibility between carbon fiber and polyurethane is solved, the mechanical properties and flame retardant properties of the material are significantly improved, and the efficient reinforcement and good performance of polyurethane materials are achieved. Flame retardant effect.

CN119331279AInactive Publication Date: 2025-01-21WEIHAI YANTUO COMPOSITE MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411446971.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The poor compatibility of carbon fiber and cellulose with polyurethane leads to poor mechanical properties and flame retardant properties of polyurethane.

Method used

Add microcrystalline cellulose and chilitate-based DOPO to N, N-di metamimamide to obtain the ester-based dopo modified cellulose; then KH570 modified carbon fiber, cymbal DOPO modified cellulose and Polyurethane acrylic is chemically cross-linking, and the pyramid-ethylene clicks are used to respond to the use of the bastylxia di methal ether light, forming a close chemical cross-linking network.

Benefits of technology

Significantly improves the interface bonding strength between carbon fiber and polyurethane, enhances the reinforcing effect of carbon fiber, improves the tensile strength and elongation at break of polyurethane materials, and gives the material good flame retardant properties, with the UL94 rating reaching V0 level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331279A_ABST
    Figure CN119331279A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon fiber composite materials, and discloses a preparation method of a modified carbon fiber composite material, KH570 modified carbon fiber, sulfydryl DOPO modified cellulose and urethane acrylate are stirred and mixed uniformly, benzoin dimethyl ether is added, and the mixture is placed under an ultraviolet lamp for irradiation reaction to obtain the modified carbon fiber composite material. The thiol DOPO modified cellulose, the alkenyl of the carbon fiber and the alkenyl of the polyurethane acrylate are subjected to thiol-ene click reaction, so that the interface bonding strength between the carbon fiber and the polyurethane acrylate is enhanced, and the tensile strength and the elongation at break of the polyurethane material are remarkably improved. The modified cellulose contains DOPO phosphaphenanthrene flame-retardant groups, phosphoric acid substances are generated through combustion, dehydration and carbonization of the cellulose and polyurethane groups can be promoted, the modified cellulose and the carbon fibers form a continuous and stable composite carbon layer, and the composite material has good flame-retardant performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber composite materials, and specifically relates to a method for preparing a modified carbon fiber composite material. Background Art

[0002] As a high-performance fiber material, carbon fiber has high strength, high temperature resistance, and good wear resistance, and is widely used in polymer materials such as plastics and rubber. Ordinary carbon fiber has poor compatibility with materials such as polyurethane, epoxy resin, and nitrile rubber, making it difficult to effectively play the reinforcing role of carbon fiber. Therefore, it is necessary to modify the surface of carbon fiber to improve its compatibility with the polymer material matrix.

[0003] Cellulose is the most abundant biomass resource in nature. It is cheap, easy to obtain, green and pollution-free. Cellulose itself has high strength and modulus. It can be used as a reinforcing agent to improve the mechanical properties of materials such as polyurethane. Patent CN105601878B Nanocellulose whisker grafted water-diluted photocurable PUA resin and its preparation and application, polyurethane prepolymer is reacted with dihydroxymethyl propionic acid, nanocellulose whiskers, hydroxypropyl acrylate and pentaerythritol triacrylate in sequence to obtain a PUA prepolymer containing nanocellulose whiskers, which has the characteristics of fast photocuring speed, good adhesion, excellent water resistance, etc. However, the cellulose in this patent does not improve the flame retardant properties of polyurethane. Summary of the invention

[0004] The invention solves the problems of poor compatibility of carbon fiber, cellulose and polyurethane, and poor mechanical properties and flame retardancy of polyurethane.

[0005] Technical solution: A method for preparing a modified carbon fiber composite material:

[0006] Step (1): Add microcrystalline cellulose to N,N-dimethylformamide, stir and mix for 3-6 hours, then add thioacetate-DOPO, co-solvent toluene, and p-toluenesulfonic acid to react, add ethanol to the solution, filter, wash the filter cake with ethanol, and dry to obtain thiocarbyl-DOPO modified cellulose.

[0007] Step (2): Add KH570 modified carbon fiber, mercapto DOPO modified cellulose and polyurethane acrylate to acetone, stir and mix for 4-6 hours, then add benzoin dimethyl ether, pour into a glass mold, place under ultraviolet light for irradiation reaction, and dry to obtain a modified carbon fiber composite material.

[0008] Preferably, in step (1), the mass ratio of microcrystalline cellulose, thioacetate-DOPO and p-toluenesulfonic acid is 100:(40-200):(3-18).

[0009] Preferably, in step (1), the volume ratio of N,N-dimethylformamide to toluene is 100:(20-50).

[0010] Preferably, the reaction temperature in step (1) is controlled to be 80-100° C., and the reaction time is controlled to be 6-18 h.

[0011] Preferably, in step (2), the mass ratio of KH570 modified carbon fiber, mercapto DOPO modified cellulose, polyurethane acrylate, and benzoin dimethyl ether is (0.5-3):(4-25):100:(0.06-0.35).

[0012] Preferably, in step (2), the power of the ultraviolet lamp is 800-1000W, and the irradiation time is 1-4h.

[0013] Preferably, the preparation method of thioacetate-DOPO in step (2) is:

[0014] S1: Add pyridine, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, and 4-formylbenzoyl chloride in a molar ratio of (2-2.4):1:(2-2.3) to toluene, heat to 35-55°C, react for 10-15h, concentrate the solution, wash with acetone, and recrystallize the product in chloroform to obtain benzoyl DOPO-HQ.

[0015] S2: Add cysteine ​​and potassium hydroxide to ethanol, heat and stir to dissolve, add an ethanol solution containing benzoyl DOPO-HQ, wherein the molar ratio of cysteine, potassium hydroxide and benzoyl DOPO-HQ is (1.9-2.1):(1.9-2.1):1; react at 40-50°C in a nitrogen atmosphere for 6-10 hours, add dilute hydrochloric acid to adjust the pH of the solution to 6, concentrate the solution, wash with water and acetone in turn, and recrystallize the product in chloroform to obtain thioacetate-DOPO.

[0016] Preferably, the preparation method of KH570 modified carbon fiber is: placing the carbon fiber into a mixed acid of concentrated sulfuric acid and concentrated nitric acid for oxidation to obtain oxidized carbon fiber; then adding the oxidized carbon fiber to ethanol, ultrasonically dispersing it, adding dilute hydrochloric acid to adjust the pH to 4, adding KH570 ethanol solution, filtering after reaction, washing with ethanol and water in turn, and drying to obtain KH570 modified carbon fiber.

[0017] Technical effect: The present invention uses 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, 4-formylbenzoyl chloride and cysteine ​​as reactions to prepare a thioacetic acid-based DOPO monomer containing carboxyl and thiol groups, and then uses p-toluenesulfonic acid as a catalyst to cause an esterification reaction between the carboxyl group and the hydroxyl group of microcrystalline cellulose to obtain thiol-DOPO modified cellulose, thereby introducing active thiol groups and DOPO phosphaphenanthrene flame retardant groups into the cellulose molecular chain.

[0018] In the polyurethane acrylate of the present invention, KH570 modified carbon fiber and mercapto DOPO modified cellulose are added, and under the action of benzoin dimethyl ether photoinitiator, the mercapto group of the modified cellulose and the alkenyl group of the carbon fiber and the alkenyl group of the polyurethane acrylate undergo mercapto-ene click reaction, so that the mercapto DOPO modified cellulose is used as a crosslinking agent, and the KH570 modified carbon fiber and the polyurethane acrylate are chemically crosslinked, thereby enhancing the interface bonding strength between the carbon fiber and the polyurethane acrylate, making the carbon fiber have a better reinforcement effect, and significantly improving the tensile strength and elongation at break of the polyurethane material. In addition, the microcrystalline cellulose itself also has the characteristics of high strength and high modulus, and after chemically crosslinking with the polyurethane acrylate, it also has an improving effect on the tensile strength of the polyurethane material.

[0019] The modified cellulose of the present invention contains DOPO phosphaphenanthrene flame retardant groups, which burn to produce phosphoric acid substances, which can promote the dehydration and carbonization of cellulose and polyurethane groups, and form a composite continuous and stable composite carbon layer with carbon fibers, which can hinder the contact between oxygen and the material matrix and inhibit the combustion process. At the same time, it can hinder heat conduction and inhibit the release of smoke during combustion, so that the composite material has good flame retardant properties, shows a higher limiting oxygen index, and the UL94 grade reaches V0 grade.

[0020] The present invention utilizes mercapto DOPO modified cellulose to carry out cross-linking reaction on polyurethane acrylate and KH570 modified carbon fiber, so as to form a tight chemical cross-linking network in the polyurethane molecular chain, which is beneficial to inhibiting water molecules from entering into the polyurethane material matrix, thereby reducing the water absorption rate of the polyurethane and improving its water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the reaction formula for the preparation of thioacetate-DOPO.

[0022] Figure 2 This is the reaction formula for preparing mercapto DOPO-modified cellulose. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The polyurethane acrylate of the present invention has a brand number of SW3673, a content of 99%, and is produced by Wuhan Huaxiang Kejie Biotechnology.

[0025] Microcrystalline cellulose, content 99%, Wuhan Jiyesheng Chemical.

[0026] Carbon fiber, thickness 6-7um; Shanghai Lishuo Composite Materials Technology.

[0027] Example 1

[0028] (1): Add 8 mmol pyridine, 4 mmol 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide (CAS No. 99208-50-1), and 9.2 mmol 4-formylbenzoyl chloride (CAS No. 16173-52-7) to 20 mL of toluene, heat to 35°C, react for 15 hours, concentrate the solution, wash with acetone, and recrystallize the product in chloroform to obtain benzoyl DOPO-HQ.

[0029] (2): Add 10.5 mmol of cysteine ​​(CAS No. 374-22-9) and 10.5 mmol of potassium hydroxide to 60 mL of ethanol, heat and stir to dissolve, add 20 mL of ethanol solution containing 5 mmol of benzoyl DOPO-HQ; react at 40° C. in a nitrogen atmosphere for 6 h, add dilute hydrochloric acid to adjust the pH of the solution to 6, concentrate the solution, wash with water and acetone in turn, and recrystallize the product in chloroform to obtain thioacetate-DOPO.

[0030] (3): Add 5 g of microcrystalline cellulose to 80 mL of N,N-dimethylformamide, stir and mix for 3 h, then add 10 g of thioacetate-DOPO, 30 mL of toluene as a co-solvent, and 0.15 g of p-toluenesulfonic acid, heat to 90 ° C, react for 18 h, add ethanol to the solution, filter, wash the filter cake with ethanol, and dry to obtain thio-DOPO-modified cellulose.

[0031] (4): 3g of carbon fiber was placed in a mixed acid of 30mL of concentrated sulfuric acid (mass fraction 98%) and 10mL of concentrated nitric acid (mass fraction 60%), heated to 80°C, oxidized for 6h, filtered, washed with water, and dried to obtain oxidized carbon fiber; then the oxidized carbon fiber was added to 40mL of ethanol, ultrasonically dispersed, diluted hydrochloric acid was added to adjust the pH to 4, 15mL of ethanol solution containing 2g of KH570 was added, heated to 60°C for reaction for 24h, filtered, washed with ethanol and water in turn, and dried to obtain KH570 modified carbon fiber.

[0032] (5): Add 0.5 g KH570 modified carbon fiber, 4 g mercapto DOPO modified cellulose, and 100 g polyurethane acrylate to 150 mL acetone, stir and mix for 4 h, then add 0.06 g benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for irradiation reaction for 1 h, and dry to obtain a modified carbon fiber composite material.

[0033] Example 2

[0034] (1): Add 9.6 mmol pyridine, 4 mmol 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, and 9.2 mmol 4-formylbenzoyl chloride to 25 mL toluene, heat to 55°C, react for 10 hours, concentrate the solution, wash with acetone, and recrystallize the product in chloroform to obtain benzoyl DOPO-HQ.

[0035] (2): Add 9.5 mmol cysteine ​​and 9.5 mmol potassium hydroxide to 60 mL ethanol, heat and stir to dissolve, add 20 mL ethanol solution containing 5 mmol benzoyl DOPO-HQ; react at 50°C in a nitrogen atmosphere for 10 h, add dilute hydrochloric acid to adjust the pH of the solution to 6, concentrate the solution, wash with water and acetone in turn, and recrystallize the product in chloroform to obtain thioacetate-DOPO.

[0036] (3): Add 5 g of microcrystalline cellulose to 80 mL of N,N-dimethylformamide, stir and mix for 6 h, then add 6 g of thioacetate-DOPO, 20 mL of toluene as a co-solvent, and 0.54 g of p-toluenesulfonic acid, heat to 80 ° C, react for 18 h, add ethanol to the solution, filter, wash the filter cake with ethanol, and dry to obtain thio-DOPO-modified cellulose.

[0037] (4): Add 1.8 g of KH570 modified carbon fiber (prepared in the same manner as in Example 1), 15 g of mercapto DOPO modified cellulose, and 100 g of polyurethane acrylate to 200 mL of acetone, stir and mix for 6 hours, then add 0.2 g of benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for irradiation reaction for 2 hours, and dry to obtain a modified carbon fiber composite material.

[0038] Example 3

[0039] (1): Add 5 g of microcrystalline cellulose to 80 mL of N,N-dimethylformamide, stir and mix for 5 h, then add 2 g of thioacetate-DOPO (the same preparation method as in Example 1), 12 mL of toluene as a co-solvent, and 0.15 g of p-toluenesulfonic acid, heat to 100 ° C, react for 6 h, add ethanol to the solution, filter with suction, wash the filter cake with ethanol, and dry to obtain thioacetate-DOPO-modified cellulose.

[0040] (2): Add 3 g of KH570 modified carbon fiber (prepared in the same manner as in Example 1), 25 g of mercapto DOPO modified cellulose, and 100 g of polyurethane acrylate to 200 mL of acetone, stir and mix for 6 hours, then add 0.35 g of benzoin dimethyl ether, pour into a glass mold, place under an 800 W ultraviolet lamp for irradiation reaction for 4 hours, and dry to obtain a modified carbon fiber composite material.

[0041] Comparative Example 1

[0042] The main difference between this comparative example and Example 1 is that KH570 modified carbon fiber and mercapto DOPO modified cellulose are not added.

[0043] (1) Add 100 g of polyurethane acrylate to 150 mL of acetone, stir and mix for 4 h, then add 0.06 g of benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for 1 h, and dry to obtain a polyurethane material.

[0044] Comparative Example 2

[0045] The main difference between this comparative example and Example 1 is that KH570 modified carbon fiber is not added.

[0046] (1) Add 4 g of mercapto DOPO-modified cellulose and 100 g of polyurethane acrylate to 150 mL of acetone, stir and mix for 4 h, then add 0.06 g of benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for irradiation reaction for 1 h, and dry to obtain a polyurethane material.

[0047] Comparative Example 3

[0048] The main difference between this comparative example and Example 1 is that carbon fiber not modified with KH570 is added.

[0049] (1): Add 0.5 g carbon fiber, 4 g mercapto DOPO modified cellulose, and 100 g polyurethane acrylate to 150 mL acetone, stir and mix for 4 h, then add 0.06 g benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for irradiation reaction for 1 h, and dry to obtain a modified carbon fiber composite material.

[0050] Comparative Example 4

[0051] The main difference between this comparative example and Example 1 is that no mercapto DOPO-modified cellulose is added.

[0052] (1): Add 0.5 g KH570 modified carbon fiber and 100 g polyurethane acrylate to 150 mL acetone, stir and mix for 4 h, then add 0.06 g benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for irradiation reaction for 1 h, and dry to obtain a modified carbon fiber composite material.

[0053] Comparative Example 5

[0054] The main difference between this comparative example and Example 1 is that unmodified microcrystalline cellulose is added.

[0055] (1): Add 0.5 g KH570 modified carbon fiber, 4 g microcrystalline cellulose, and 100 g polyurethane acrylate to 150 mL acetone, stir and mix for 4 h, then add 0.06 g benzoin dimethyl ether, pour into a glass mold, place under a 1000 W ultraviolet lamp for irradiation reaction for 1 h, and dry to obtain a modified carbon fiber composite material.

[0056] The tensile properties of composite materials were tested according to GB / T 1040.1-2018 method.

[0057] The composite material was made into a sample of 10cm×10cm×5mm, dried, weighed, and then immersed in water for 24h. The sample was taken out, the surface moisture was absorbed with filter paper, and the sample was weighed to calculate the water absorption rate R.

[0058] R=(mm 0 ) / m×100%. m is the mass of the composite material after absorbing water. 0 It is the mass of the composite material before absorbing water. The test results are shown in the following table.

[0059]

[0060]

[0061] KH570 modified carbon fiber and mercapto DOPO modified cellulose are added to the polyurethane acrylate of Examples 1-3. Under the action of benzoin dimethyl ether photoinitiator, the mercapto group of the modified cellulose undergoes a mercapto-ene click reaction with the olefin group of the carbon fiber and the olefin group of the polyurethane acrylate, thereby using the mercapto DOPO modified cellulose as a cross-linking agent to chemically cross-link the KH570 modified carbon fiber and the polyurethane acrylate, thereby enhancing the interfacial bonding strength between the carbon fiber and the polyurethane acrylate, making the carbon fiber have a better reinforcement effect, and significantly improving the tensile strength and elongation at break of the polyurethane material. In addition, the microcrystalline cellulose itself also has the characteristics of high strength and high modulus, and after chemically cross-linking with the polyurethane acrylate, it also improves the tensile strength of the polyurethane material. In addition, the modified cellulose contains DOPO phosphaphenanthrene flame retardant groups, which produce phosphoric acid substances when burned, which can promote the dehydration and carbonization of cellulose and polyurethane groups, and form a composite continuous and stable composite carbon layer with carbon fibers, which can hinder the contact between oxygen and the material matrix and inhibit the combustion process. At the same time, it can hinder heat conduction and inhibit the release of smoke during combustion, so that the composite material has excellent flame retardant properties and exhibits a higher limiting oxygen index. The UL94 grade reaches V0 level.

[0062] By using mercapto DOPO-modified cellulose to cross-link polyurethane acrylate and KH570 modified carbon fiber, a tight chemical cross-linking network is formed in the polyurethane molecular chain, which is beneficial to inhibit the entry of water molecules into the polyurethane material matrix, thereby reducing the water absorption rate of polyurethane and improving its water resistance.

[0063] Comparative Example 1 did not add KH570 modified carbon fiber and mercapto DOPO modified cellulose, the tensile strength and elongation at break of the polyurethane material were low, the mechanical properties were poor, the limiting oxygen index was only 17.4, there was no UL94 grade, and the flame retardant properties were very poor.

[0064] In Comparative Example 2, KH570 modified carbon fiber is not added, but mercapto DOPO modified cellulose is added. Under the action of benzoin dimethyl ether photoinitiator, the mercapto group and the olefinic group of polyurethane acrylate undergo mercapto-olefin click reaction to achieve crosslinking of the polyurethane, thereby forming a tight chemical crosslinking network, which is beneficial to reducing the water absorption rate of the polyurethane. Compared with Comparative Example 1, the tensile strength and limiting oxygen index of the polyurethane are significantly improved, the UL94 grade is V1 grade, and the flame retardant performance is excellent.

[0065] The carbon fiber of Comparative Example 3 has not been modified with KH570, and does not contain olefin groups, and cannot undergo chemical crosslinking reaction with polyurethane acrylate, resulting in poor compatibility of the carbon fiber with the polyurethane material, and the tensile strength and elongation at break are significantly lower than those in Example 1.

[0066] In Comparative Example 4, no mercapto DOPO-modified cellulose is added, and the KH570-modified carbon fiber cannot undergo a chemical crosslinking reaction with polyurethane acrylate. However, after the carbon fiber is organically modified by KH570, its compatibility with the polyurethane material is also improved to a certain extent. Compared with Comparative Example 1, the tensile properties of the polyurethane material are improved to a certain extent, and the limiting oxygen index is slightly increased. It can be seen that the addition of carbon fiber is beneficial to improving the flame retardant properties of the polyurethane material. However, its water absorption rate is higher than that of Example 1, and the limiting oxygen index is lower than that of Example 1.

[0067] Comparative Example 5 adds unmodified microcrystalline cellulose, which does not contain olefin groups and cannot undergo chemical crosslinking reaction with KH570 modified carbon fiber and polyurethane acrylate, does not reduce the water absorption rate of polyurethane, and the microcrystalline cellulose does not contain DOPO phosphaphenanthrene flame retardant groups, does not improve the limiting oxygen index and flame retardant properties of polyurethane.

[0068] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing a modified carbon fiber composite material, characterized in that: The preparation method is: Step (1): adding microcrystalline cellulose to N,N-dimethylformamide, stirring and mixing, adding thioacetate-DOPO, co-solvent toluene, and p-toluenesulfonic acid, reacting, adding ethanol to the solution, filtering, washing, and drying to obtain thio-DOPO-modified cellulose; Step (2): Add KH570 modified carbon fiber, mercapto DOPO modified cellulose, and polyurethane acrylate to acetone, stir and mix, then add benzoin dimethyl ether, pour into a mold, place under ultraviolet light for irradiation reaction, and dry to obtain a modified carbon fiber composite material.

2. The method for preparing a modified carbon fiber composite material according to claim 1, characterized in that: In the step (1), the mass ratio of microcrystalline cellulose, thioacetate DOPO and p-toluenesulfonic acid is 100:(40-200):(3-18).

3. The method for preparing a modified carbon fiber composite material according to claim 1, characterized in that: In the step (1), the volume ratio of N,N-dimethylformamide to toluene is 100:(20-50).

4. The method for preparing a modified carbon fiber composite material according to claim 1, characterized in that: In the step (1), the reaction temperature is controlled to be 80-100° C., and the reaction time is controlled to be 6-18 hours.

5. The method for preparing a modified carbon fiber composite material according to claim 1, characterized in that: In the step (2), the mass ratio of KH570 modified carbon fiber, mercapto DOPO modified cellulose, polyurethane acrylate and benzoin dimethyl ether is (0.5-3):(4-25):100:(0.06-0.35).

6. The method for preparing a modified carbon fiber composite material according to claim 1, characterized in that: In the step (2), the power of the ultraviolet lamp is 800-1000W, and the irradiation time is 1-4h.

7. The method for preparing a modified carbon fiber composite material according to claim 5, characterized in that: The preparation method of thioacetate-DOPO in step (2) is: S1: Add pyridine, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, and 4-formylbenzoyl chloride to toluene, heat to 35-55°C, react for 10-15h, concentrate the solution, wash, and recrystallize to obtain benzoyl DOPO-HQ; S2: Add cysteine ​​and potassium hydroxide to ethanol, heat and stir to dissolve, add ethanol solution containing benzoyl DOPO-HQ, react at 40-50°C in a nitrogen atmosphere for 6-10 hours, add dilute hydrochloric acid, concentrate the solution, wash, and recrystallize to obtain thioacetate DOPO.

8. The method for preparing a modified carbon fiber composite material according to claim 7, characterized in that: The molar ratio of pyridine, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, and 4-formylbenzoyl chloride in S1 is (2-2.4):1:(2-2.3).

9. The method for preparing a modified carbon fiber composite material according to claim 7, characterized in that: The molar ratio of cysteine, potassium hydroxide and benzoyl DOPO-HQ in S2 is (1.9-2.1):(1.9-2.1):

1.

10. The method for preparing a modified carbon fiber composite material according to claim 5, characterized in that: The preparation method of the KH570 modified carbon fiber is as follows: the carbon fiber is placed in a mixed acid of concentrated sulfuric acid and concentrated nitric acid for oxidation to obtain oxidized carbon fiber; the oxidized carbon fiber is then added to ethanol, ultrasonically dispersed, diluted hydrochloric acid and KH570 ethanol solution are added, and after reaction, the carbon fiber is filtered, washed, and dried to obtain the KH570 modified carbon fiber.

Citation Information

Patent Citations

  • Nanocellulose whiskers grafted with water-diluted photocurable PUA resin and its preparation and application

    CN105601878B

Cited By

  • High-temperature-resistant and anti-freezing PVDF (polyvinylidene fluoride) plate as well as preparation method and application thereof

    CN119955237A